Refleksi Putusan Bebas Kasus Korupsi dan Illegal Logging dalam Perspektif Hak-hak Azasi Manusia - Rusli Muhammad (Unisia, 2007)
Court decisions releasing the accused both in the cases of corruption and those of illegal logging could be influenced by juridical factor, for example the regulation on the criteria for decisions releasing the accused. This regulation would be a guide for judges. Besides, court decisions releasing the accused could also be influenced by non-juridical factor, such as return fee payment. The implication of such decisions on human rights is that the conducts of corruption and illegal logging tend to decrease and destruct the economic life, safety, peace, and welfare of people. The ideal judge decisions should be combination of normative, philosophical, and sociological considerations. These could be done by highly integrated, professional, progressive and knowledgeable judges who believe in God. Keywords: Court Decisions, Corrup-tion, Human Rights, Illegal logging, Release